Community Views on Changing Religions as a Reason for Marriage in a Review of Islamic Law in Beringin Jaya Village, Baebunta District, North Luwu Regency - Aini, Qurratul; Muchtar, M Ilham; Abidin, Zainal (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2023)
Conversion in Islam is known as apostasy. This conversion is not uncommon, including the incident that has occurred in Beringin Jaya Village, Baebunta District, North Luwu Regency.some are With this, researchers divide into several subproblems including: how is the description of the conversion process in Beringin Jaya Village, Baebunta District, North Luwu Regency? and how to convert in the view of the people of Beringin Jaya Village, Baebunta District, North Luwu Regency according to Islamic law? This type of research is field research where this research is carried out by going directly into the field to obtain data from informants related to the research conducted. This research is presented in a descriptive form with the aim of describing the processes that occur in the field. While the approach taken is a qualitative approach. The data collection techniques used were abconservation, interviews and documentation. The results of this study show that religious conversion carried out by people in Beringin Jaya Village is based on marriage, because they love their partners too much so they sacrifice the ir religion to follow their partner's religion. That is by holding a wedding that previously Hinduism converted to Islam. And the process of converting to Islam is before they get married, some convert to Islam after the proposal is accepted and some convert to Islam before the proposal is accepted.